PENGARUH LABA DAN ARUS KAS TERHADAP FINANCIAL DISTRESS: Studi Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2020 - Eva Ahmad; Thiar Millati Hanifan (JURNAL AKUNTANSI DAN SISTEM INFORMASI, 2022)
Financial distress is a condition where the company cannot pay its obligations. Financial distress is a financial difficulty experienced by a company but has not yet gone bankrupt. Therefore, it is important for companies to identify financial distress conditions first as evaluation material and early warning. This study aims to examine the effect of earnings and cash flow on financial distress. The population in this study is the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018- 2020, totaling 26 companies. The sample in this study uses a purposive sampling technique where it has been determined that the food and beverage sub-sector manufacturing companies listed on the BEI that meet the criteria are 18 companies so that the number of samples used from 2018-2020 is 54 companies. The analytical tool used in this research is multiple linear regression analysis and the coefficient of determination. Starting with the classical assumption test, then a hypothesis test was carried out which was processed using the SPSS version 25 for Windows program. The results of this study indicate that profit and cash flow have an effect on financial distress either partially or simultaneously